Langue décalée et effacement référentiel dans „La Ville à voile” de Paul Willems (1966) - Chéron, Sophie (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2014)
Paul Willems (1912-1997) is a French-speaking writer from Flanders who received the Quinquennial Award of French Literature from Belgium for his oeuvre in 1980. His work is set in the literary current of Belgitude, a discourse involving the ambiguous rapport between a devalued native culture (Belgian culture in French) and an exterior standardized culture (French culture from France). Through an analysis of language and space in The Sailing City, I argue that Willems claims a cultural degeneration (typical for Belgitude) in order to reassert a unique Belgian identity. This identity is not based on a defined language and a space – as Willems thinks it would be for the expression of French identity, shaped by a standardized language and explicit spacial references. In Willems’s play, language standardization and spatial references are erased to define a Belgian identity by what it is not rather than by what it is.